Implementasi Prinsip Ekonomi Islam pada Era Al-Khulafa’ Al-Rasyidin - Anggi Pretty Nadya Rumapea; Sadepa Putri Br Sunulingga; Tiara Tirta Dewi; Tio Wirayuda; Fitri Hayati (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This research discusses the application of Islamic economic principles during the leadership of Al-Khulafa' Al-Rasyidin, namely Abu Bakar Ash-Shiddiq, Umar bin Khattab, Uthman bin Affan, and Ali bin Abi Talib. The focus of the study lies on the application of sharia values such as justice, honesty, zakat, and wealth distribution in economic policy and governance. The study found that the caliphs consistently implemented Islamic economic principles in state financial management, zakat collection and distribution, market supervision, and protection of property rights. Such implementation proved the effectiveness of the Islamic economic system in creating social justice and public welfare. The application of Islamic economic principles in financial management has an important role because it provides a strong ethical and moral basis, supports the creation of a sustainable economy, and emphasizes justice in the distribution of wealth in society. These principles serve as guidelines for individuals to manage their finances wisely so as to bring benefits not only to themselves, but also to their social environment. By applying these values, wealth inequality can be prevented and a stable and fair economic system can be built. Islamic economics also emphasizes the importance of transparency and honesty in every financial transaction. By avoiding unethical practices such as usury and excessive speculation, individuals can maintain integrity and create a financial system that is aligned with moral values. In addition, Islamic economic principles contain a high value of social responsibility, reflected in the teachings on Zakat, Infaq, and Sadaqah which encourage individuals to participate in social development and help those in need. Therefore, managing personal finances based on these principles not only ensures individual financial sustainability, but also has a positive impact on the well-being of society at large.